Pandangan Imam Al-Mawardi tentang Wizarah dan Kedudukan Wazir - Masyrofah Masyrofah; Gilang Rizki Aji Putra (ADALAH, 2022)
Draft The ministry, according to Imam Al-Mawardi, is stated in his work entitled Al-Ahkam Al-Shulthaniyah. Imam Al-Mawardi divides the concept of the wizard (Ministry) into two, namely wizarah tafwidh and wizarah tanfidzh. From the two concepts of Imam Al Mawardi, there is a correlation between the concept of wizarah (Ministry) tanfizh with the concept of the Ministry in Indonesia. The difference is that there were no political parties during Imam Al-Mawardi's time, while In Indonesia, there are political parties.